Compensation Planning In Increase Employee Performance - Agus Suharyadi; Agus Hidayat; Ahmad Faisal; Hadi Supratikta (Indonesian Development of Economics and Administration Journal, 2023)
This research is a literature study, which is carried out through journal reviews and literature studies that are relevant to the research. The type of data used is secondary data, namely data obtained indirectly. Data collection techniques are carried out by reviewing and analyzing books and journals with rules related to planning gift compensation. From the results of this study it is known that planning gift compensation very important. Human Resources a organization, claim era revolution inside 4.0 and era competition free moment This expected organization must own source one man Which quality, innovative and creative. Because organization is network and decision for successor policy and recruitment decision. Compensation used as reject measuring performance with objective get employee which quality, maintain employee and give contribution Which Good for organization. The industrial revolution 4.0 has brought so many changes, especially changes in very fast technological developments which greatly affect the world of work, namely humans are required to master technology, especially for officer in company Which direct relate with data employee. And companies are also required to be able to keep abreast of these technological developments and adapt them to activities gift compensation at the company. So that speed up process gift compensation as well as increase performance employee